ISLAMIC PERSPECTIVE AT THE CONSUMPTION ETHICS OF STUDENTS IN AN-NIDA SALATIGA ISLAMIC BOARDING IN THE COVID-19 PANDEMIC - Choirul Amirudin; Ahmad Fikri Sabiq (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2022)
This study aims to determine the ethical patten of consumption of the Islamic students at An-Nida Islamic boarding school. The research was conducted in November 2020 using google form and other reputable journals with the keyword